一种林地自动识别分类方法、设备及存储设备 (2025)
本发明公开了一种林地自动识别分类方法、设备及存储设备，方法具体如下：获取真正射影像和高密度LiDAR点云数据，并进行预处理，获得预处理后的数据；对预处理后的数据进行点云选取，得到林冠层二维点云数据；计算林冠层二维点云数据的郁闭度，并根据郁闭度自动识别林地；对林地进行属性标注；完成拓扑检查和数据修正。本发明有益效果是：本发明综合利用遥感影像和高密度LiDAR点云数据的空间邻近特征，过滤了非目标地类的点云数据，实现了有林地的快速、精确、智能识别和提取，有效节约信息提取时间，提高工作效率；本发明的执行步骤具有简洁性、可操作性、人工参与度低等特点，为林地资源的开发保护、资源监测、资源管理提供了新的技术支撑。 The invention discloses a forest land automatic identification and classification method and device, and a storage device, and the method specifically comprises the following steps: obtaining a true shoot image and high-density LiDAR point cloud data, and carrying out the preprocessing, and obtaining the preprocessed data; performing point cloud selection on the preprocessed data to obtain forest canopy two-dimensional point cloud data; calculating the canopy density of the two-dimensional point cloud data of the canopy, and automatically identifying the forest land according to the canopy density; carrying out attribute labeling on the forest land; and topology check and data correction are completed. The bene